Letter (copy) : Goods for Bilbao - Tewson, Vincent
029-0156-001 ST/HO.6809 HVT/EAB/703 International. 4th May 1937. Mr. J. Thompson, Co-operative Wholesale Society Limited, 1, Balloon Street, Manchester 4. Dear Mr. Thompson, GOODS FOR BILBAO. We have received your letters of the 26th April and 3rd May, in which you enclose your invoices in respect of goods shipped by s.s. BACKWORTH from Immingham to Bilbao. We are enclosing our cheque for £2277. 3. 5. representing the invoice totals less 5/6 as per your Credit Note (39/1113 - 20.4.37) attached. We shall be glad to have your receipt in due course. We would like to take this opportunity of thanking you for the assistance you have rendered in this matter, and to say how we appreciate the trouble you have taken in securing the shipment of these goods to our Spanish comrades. Yours sincerely, Assistant Secretary. Cheque £2277. 3.5. Invoices. Credit Note. 292/946/29/156